2018
DOI: 10.4081/aiua.2018.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Utility of uroflowmetry during the follow-up of children affected by balanitis xerotica obliterans (BXO)

Abstract: We recommend to send for hystological examination all foreskins excised after circumcision. We believe that a clinical and uroflowmetric follow-up of pediatric patients with BXO is mandatory for a prompt identification of post-voiding dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Snodgrass et al 86 found 40% of patients who had circumcision for meatal LS (complete excision, including total replacement of the involved urethra) still had a recurrence of the disease at a median of 2 years. The progression of LS in boys can lead to obstructive urinary tract complications, and in severe cases, even renal failure 85,87 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Snodgrass et al 86 found 40% of patients who had circumcision for meatal LS (complete excision, including total replacement of the involved urethra) still had a recurrence of the disease at a median of 2 years. The progression of LS in boys can lead to obstructive urinary tract complications, and in severe cases, even renal failure 85,87 …”
Section: Resultsmentioning
confidence: 99%
“…LS can be a chronic disease, as seen in the recurrence rate in both sexes after either initial topical therapy in girls or circumcision in boys. 33,35,69,72,[78][79][80][81][82][83][84][85][86][87][88][97][98][99] As discussed earlier, literature often refers to meatal and urethral strictures post-surgery as complications of the circumcision. In our practice, however, we note the meatus is involved prior to circumcision in nearly all cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations